Structural, morphological, optical, and photoluminescence properties of piperine thin films deposited by spin-coating technique - Mohd Sarjidan, M. A.; Azlan, A.; Razak, F. A. (Elsevier BV, 2021)
In this paper, the structural, morphological, optical, and photoluminescence (PL) properties of piperine thin film have been investigated. The structural and morphological studies show that spin-coating methods can produce a high-quality piperine thin film from a solution. The optical and PL analysis revealed that the piperine exhibits a high band-gap above 3 eV and produces strong blue emission under 330 nm excitation. Moreover, the piperine can transfer an energy to tune the luminescence properties of poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV) thin film. The properties of piperine thin film obtained from this study seem very promising for applications in optoelectronic devices.